Election : a novel - Perrotta, Tom, 1961- (Berkley Books, 1998)
New Jersey high school teacher Mr. McAllister faces a personal and professional crisis when he decides to fix the student body election, while at the same time dealing with an unexpected attraction to his wife's best friend.